Palynological correlation of Mississippian (Carboniferous) stages in Western Europe and the USA - Heal, Sarah E. (Trinity College (Dublin, Ireland). Department of Geology, 2009)
Palynological assemblages from the Late Devonian - Mississippian of Kentucky and the Mississippi Valley have been studied. Productive samples have been obtained from two outcrops situated in northeast Kentucky and eight outcrops and 21 cores from Illinois, Missouri and Iowa in the Mississippi Valley. Spores, acritarchs, prasinophytes and scolecodonts have been recovered. The miospores, acritarchs and prasinophytes have been systematically described and illustrated. In total, 124 miospore taxa have been recognised. Eight species and a single spore type have been described in open nomenclature. Twenty- seven acritarch taxa have been recognised.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin